Approximate expressions for the capillary force and the surface area of a liquid bridge between identical spheres - Bagheri, Meysam; Roy, Sudeshna; Pöschel, Thorsten (Computational Particle Mechanics, 2024)
We consider a liquid bridge between identical spheres and present approximate expressions for the capillary force and the exposed surface area of the liquid bridge as functions of the liquid bridge’s total volume and the sphere separation distance. The radius of the spheres and the solid–liquid contact angle are parameters that enter the expressions. These expressions are needed for efficient numerical simulations of drying suspensions and other systems involving liquid bridges whose volume or shape vary in time.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Capillary force; Liquid bridge; Surface area; Young–Laplace

Discrete Element Simulations of particles interacting via capillary forces using MercuryDPM - Bagheri, Meysam; Roy, Sudeshna; Pöschel, Thorsten (SoftwareX, 2025)
We present the implementation of two advanced capillary bridge approximations within the Discrete Element Method (DEM) framework of the open-source code MercuryDPM. While MercuryDPM already includes a simplified version of the Willett approximation, our work involves implementing both the classical Willett approximation and the recently published Bagheri approximation in MercuryDPM. Through detailed descriptions and illustrative simulations using a two-particle collision model, we demonstrate the enhanced accuracy and capabilities of these approximations in capturing the complex dynamics of wet granular matter.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Capillary force; Discrete Element Method — DEM; Liquid bridge; Particle sizes